Application of genotype-by-sequencing for diversity and genetic marker identification of hop cultivars in Brazil - Burricks, Ashley Noel (2022)
Humulus lupulus is a plant originally cultivated in Europe for their cones, which are used in the beer making process. Brazil has a large beer industry but its traditionally unsuitable climate has limited cultivation of the plant. A dedicated hop breeding program is necessary to produce unique Brazilian cultivars that are suited to the climate and are profitable for the growers. A deeper understanding of the available germplasm is necessary to build a strong foundation for breeding programs. This study seeks to meet those needs by using a genotype-by-sequencing approach; first to provide an understanding of the available genetic diversity of hops in Brazil, and second, to provide a means for discerning the accuracy of cultivar labeling. The study first isolated the Cascade reference genome as well as the bcf tools variant caller as the most suitable for the current data set. The study then used 5971 high-quality single nucleotide polymorphisms to distinguish 2 distinct populations. Four SSR markers were found, but analysis has called into question the use of these SSR markers for cultivar identification. From both the marker analysis and the diversity analysis it is clear that there has been some mislabeling among the cultivars present in Brazil, however, it is not yet possible to use these markers for cultivar identification.